2009
DOI: 10.1093/tropej/fmp070
|View full text |Cite
|
Sign up to set email alerts
|

Management of Scorpion Sting: Prazosin or Dobutamine

Abstract: Prazosin and dobutamine, both are useful drugs for management of cardiovascular features of scorpion envenomation, nevertheless, prazosin is slightly better than dobutamine in terms of faster recovery, and also because of its ease of administration and low cost of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
1
17
0
1
Order By: Relevance
“…If there is an imbalance of fluid and electrolyte or heart failure, treatment should be planned immediately. It has been reported that alpha-adrenergic blockers such as prazosin prevent heart damage related to increased catecholamine in the acute phase (9). This medical treatment improves the clinical findings in majority of patients in similar cases as this study.…”
Section: Discussionsupporting
confidence: 75%
“…If there is an imbalance of fluid and electrolyte or heart failure, treatment should be planned immediately. It has been reported that alpha-adrenergic blockers such as prazosin prevent heart damage related to increased catecholamine in the acute phase (9). This medical treatment improves the clinical findings in majority of patients in similar cases as this study.…”
Section: Discussionsupporting
confidence: 75%
“…Gupta et al44 showed that prazosin is slightly better than dobutamine in terms of faster recovery, and also because it is easier to administer. However, this could be due to the particular circumstances or scorpion species involved, given that heart failure is a late complication of scorpion envenoming.…”
Section: Management Of Scorpion Stingsmentioning
confidence: 99%
“…A different study comparing intravenous dobutamine vs. prazosin ( n  = 21, in each treatment arm, all paediatric patients) concluded that recovery was faster (especially for complications such as pulmonary oedema) with prazosin [14]. …”
Section: Resultsmentioning
confidence: 99%